Colloidal suspension rheology - Mewis, J. (Cambridge University Press, 2012)
"Colloidal suspensions are encountered in a multitude of natural, biological, and industrially relevant products and processes. Understanding what affects the flow behavior, or rheology, of colloid particles, and how these suspensions can be manipulated, is important for successful formulation of products such as paint, polymers, foods, and harmaceuticals. This book is the first devoted to the study of colloidal rheology in all its aspects. With material presented in an introductory manner, and complex mathematical derivations kept to a minimum, the reader will gain a strong grasp of the basic principles of colloid science and rheology. Beginning with purely hydrodynamic effects, the contributions of Brownian motion and interparticle forces are covered, before the reader is guided through specific problem areas such as thixotropy and shear thickening; special classes of colloid suspensions are also treated. An essential guide for academic and industrial researchers, this book is also ideal for graduate course use"-- Provided by publisher.
Keywords: Rheology.; Suspensions (Chemistry); Colloids.; elektronické knihy; electronic books